On export rivalry and the greening of agriculture: The role of eco-labels - Arnab K. Basu; Nancy H. Chau; Ulrike Grote (University of Bonn, Center for Development Research (ZEF), 2003)
Why do some countries establish their own national eco-labeling programs and some do not? In this paper, we provide both theoretical arguments and empirical evidence suggesting that the answer to this question can shed new light on three questions that have taken center-stage in the trade and environment debate: (i) does trade exacerbate the exploitation of the environment; (ii) are countries competing in export markets engaged in a race to the bottom in environmental performance; and (iii) do market-based environmental instruments benefit the rich and hurt the poor? Our analysis shows that a country's decision to adopt eco-labeling programs is systematically related to a country's: (i) stage of development, (ii) existing environmental performance in the absence of eco-labeling initiatives, and (iii) scale of production. To be appended to this set of essentially non-trade related factors is a set of additional factors that apply in the presence of export rivalry. These include (i) a country's comparative cost advantage and net export orientation, and (ii) the extent of peer or strategic interactions between export competitors.
Keywords: 330; Environmental Economics and Policy; International Relations/Trade; Umweltzeichen; Lebensmittelrecht; Umweltpolitik; Landwirtschaft; Internationaler Wettbewerb; Mehr-Länder-Modell; Allgemeines Gleichgewicht; Schätzung; Theorie; Welt